2023
DOI: 10.1038/s41413-023-00285-6
|View full text |Cite
|
Sign up to set email alerts
|

Interoceptive regulation of skeletal tissue homeostasis and repair

Yao Xiao,
Changhao Han,
Yunhao Wang
et al.

Abstract: Recent studies have determined that the nervous system can sense and respond to signals from skeletal tissue, a process known as skeletal interoception, which is crucial for maintaining bone homeostasis. The hypothalamus, located in the central nervous system (CNS), plays a key role in processing interoceptive signals and regulating bone homeostasis through the autonomic nervous system, neuropeptide release, and neuroendocrine mechanisms. These mechanisms control the differentiation of mesenchymal stem cells i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 223 publications
0
6
0
Order By: Relevance
“…Osteoclasts, multinuclear giant cells originating from bone marrow monocytes, are responsible for bone resorption. 35 In our study, BMMs as well as RAW264.7 cells, a mouse leukemia cell line of monocyte-macrophage, were both applied in the osteoclastogenesis observation. 36 The functions of osteoclasts mainly rely on the acidification of the microenvironment and secretion of enzymes such as TRAP, which is widely distributed in the skeleton system and acknowledged as a specific marker of osteoclasts.…”
Section: Discussionmentioning
confidence: 99%
“…Osteoclasts, multinuclear giant cells originating from bone marrow monocytes, are responsible for bone resorption. 35 In our study, BMMs as well as RAW264.7 cells, a mouse leukemia cell line of monocyte-macrophage, were both applied in the osteoclastogenesis observation. 36 The functions of osteoclasts mainly rely on the acidification of the microenvironment and secretion of enzymes such as TRAP, which is widely distributed in the skeleton system and acknowledged as a specific marker of osteoclasts.…”
Section: Discussionmentioning
confidence: 99%
“…It lacks self-healing ability when damaged, and in clinical practice, it usually manifests as persistent ankle pain. 24,25 As the injury gradually worsens, it will affect the upper surface of the talus, causing greater and irreversible damage to the entire ankle joint. [26][27][28] There is a research report that by collecting CT and MRI data of patients with ATFL rupture and 2-month follow-up after Broström surgery, by establishing nite element model of the foot and ankle to simulate the stress on the ankle joint of patients with ATFL injury before and after surgery during normal gait cycles (landing phase, neutral phase, off ground phase).…”
Section: Discussionmentioning
confidence: 99%
“…Skeletal interoception refers to the perception and interpretation of internal signals that are arising from skeletal system. This sensory mechanism involves the mechanical changes, biochemical signals, and proprioceptive information within bones and joints ( 21 , 22 ). However, it was known that the interoception was associated with visceral process, and recent research has showed the importance of skeletal interoception in understanding the dynamic interactions between bones and nervous system ( 23 ).…”
Section: Bone-nerve Interaction In Early Developmental Stagesmentioning
confidence: 99%